Personality theories a global view - Shiraev, Eric 1960- (SAGE Publications, Inc, 2017)
Short chapter-opening cases followed by basic facts, key developments related to the chapter's theme, and related theoretical approaches help students understand key content. Insightful coverage on how the various approaches work together shows students how theories can be applied in a range of contexts. Discussion of empirical studies outside the Western cultural tradition and across a wide range of countries contributes to students' understanding of cross-cultural influences. A separate chapter on gender discusses traditional and evolving views of sex, gender, and sexual orientation. An entire chapter on the clinical domain covers mental health, personality disorders, treatments, and applications relevant to students. Check and Apply Your Knowledge boxes include critical thinking questions that ask students to apply relevant theories to their everyday experiences. Self-reflection boxes ask students to think critically about their own lives, activities, accomplishments, and setbacks-all in the context of chapter content. Chapter-ending Visual Reviews help students understand each chapter's key concepts